Strategi Pengembangan Usahatani Stroberi (Fragaria vesca L) (Studi Kasus Di Desa Barudua Kecamatan Malangbong Kabupaten Garut) - Hardiyanto, Tito; Sahira, Gita; Sujaya, Dedi Herdiansah (Ma'soem University, 2024)
This research aims to determine: 1) internal and external factors as strengths, weaknesses, opportunities and threats in strawberry cultivation, 2) Alternative strategies for developing strawberry cultivation. This research uses a case study method in Barudua Village, Malangbong District, Garut Regency. Respondents totaled was 41 people. Search results show that: Internal strength factors that can be identified in strawberry farming are: land ownership status, having customers, good fruit quality, farming experience, existence of farmer groups, participation of farmer group members, control of local markets,. Weakness factors include low capital, low human resources, low product processing, low access to financial institutions, and farmers as price takers. Meanwhile, external opportunity factors include: the market is still wide open, availability of production facilities that are easily accessible, agro-tourism areas, natural conditions that have potential for farming development, availability of transportation facilities, distance of farming locations to public roads, availability of land for farming development. Meanwhile, external threats include extreme or erratic weather, perishable agricultural products, lack of agro-industry partners, high price instability, supply from other regions, disruption due to pests and weeds. A good alternative strategy to apply in developing strawberry cultivation is to use the S-O strategy, where strawberry farmers can produce strategies that use their strengths to take advantage of existing opportunities. The S-O strategy has been formulated as follows: Farmer groups collaborate with third parties, expand land, regulate village regulations, diversify product.